Instagram - Gilliard, Debora; Baalbaki-Yassine, Sally; Hoffman, David Lynn (Journal of Marketing Development and Competitiveness, 2023)
This case explores the rise of Instagram from its founder’s desire to share photos of his passion to successful funding, launch, and eventual purchase by Facebook and Mark Zuckerberg. Starting from an application, it is now a successful technology company. The case provides students with an example of a successful technological innovation, launch, development of an enterprise, and eventual harvest. While the company is popular among some users, younger generations may grow tired and see it as it as an “older” user’s platform as they now view Facebook. Can the company maintain its popularity, continued growth, and withstand governmental, societal, and parental concerns?